Postpartum Depression Among Asian Indian Mothers. Issue 4 (July 2015) - Goyal, Deepika; Park, Van Ta; McNiesh, Susan
Abstract: Purpose: To explore Asian Indian mothers' perspectives of postpartum depression (PPD) and mental health help-seeking behavior. Study Design: Qualitative exploratory design. Methods: Using convenience sampling, postpartum mothers were recruited through flyers posted in public places and on social media sites. Postpartum depression risk was assessed with the Edinburgh Postnatal Depression Scale (EPDS) prior to qualitative interviews. Content analysis methods were used to extract themes from participant narratives. Results: Twelve self-identified, married, Asian Indian mothers, aged between 29 and 40 years, living in Northern California, who gave birth to a healthy infant within the last 12 months, took part in this study. Scores on the EPDS indicated two participants were at an increased risk for developing PPD. Content analysis revealed two emerging themes: (1) Culture-specific postpartum practices and ceremonies and their role in maternal–infant postpartum recovery; and (2) Maternal mental health help-seeking behavior. Clinical Implications: Nurses taking care of women during the extended prenatal and postpartum period have the unique opportunity to build rapport with their patients which can offer a window of opportunity to educate and help dispel myths about PPD symptoms and treatment. To promote successful maternal-infant outcomes, PPD education should be initiated at the first prenatal appointment, continue during the pregnancy, and be incorporated into well-baby visits through the first postpartum year. Education should include signs and symptoms of PPD as well as importance of timely mental-health help-seeking. Abstract : Cultural patterns of Asian Indians influence perceptions and biases about mental health and clinical treatment. Asian Indian women may seek advice from their social support networks, familial ties, and religious/spiritual outlets before seeking professional help for postpartum depression.